Synopsis: Subnational public expenditures, short term household level welfare, and economic resilience: Evidence from Nigeria - Takeshima, Hiroyuki; Balana, Bedru; Smart, Jenny; Edeh, Hyacinth O.; Oyeyemi, Motunrayo Ayowumi; Andam, Kwaw S. (International Food Policy Research Institute, 2021)
This study estimates the effects of the shares of subnational public expenditure (PE) for agriculture, health, education, and social-welfare, as well as PE-size, on household-level outcomes, using nationally representative panel household data and district and state-level PE data for Nigeria. We find that greater shares of total PE allocated to agriculture, health, and social-welfare, conditional on PE-size, generally have positive effects on household consumption levels, poverty reduction, and non-farm business capital investments by households. A greater share of total PE for agriculture also positively benefits household dietary diversity across seasons. Moreover, household economic resilience, measured in terms of the economic flexibility a household has to shift between farming and non-farm activities, is more greatly enhanced through greater shares of total PE going towards agriculture than to health and social-welfare. These multi-dimensional benefits of greater PE for agriculture are particularly worthy of attention in countries, like Nigeria, which have historically allocated a low share of total PE to agriculture.